Price-quality relationships for the main livestock feed types in the Ethiopian feed market - Melesse, Adey; Bezabih, Melkamu; Adie, Aberra; Asmare, Yonas; Prasad, Kodukula V. S. V.; Devulapalli, Ravi; Jones, Chris S.; Blummel, Michael; Hanson, Jean; Alemu, Tesfaye; Duncan, Alan J. (Frontiers in Animal Science, 2023)
This study assessed the price-quality relationships for the major feed products in Ethiopia with a view to informing policy makers on possible avenues to develop the livestock feed sector in the country. A survey of livestock feed markets was conducted from April to May 2019 in five regions (Amhara, Southern Nations Nationalities and Peoples Region (SNNPR), Oromia, Tigray and Addis Ababa). A total of 1700 feed samples with their respective price information were collected from 202 marketplaces. The collected samples were analysed for their crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), in vitro organic matter digestibility (IVOMD) and metabolisable energy (ME) content. Results showed considerable variability in quality within the same feed type. Pearson correlation and regression analyses showed that price-quality relationships for the feed samples were either very weak or non-existent. Wheat bran showed a weak price to quality correlation for CP (r= 0.200 at P<0.01), ME (r= 0.202 at P<0.01) and IVOMD (r= 0.221 at P<0.01). Among the roughages, grass hay showed slight positive price to ME correlation (r= 0.382 at P<0.001) and a slight negative relationship with ADF (r=-0.336 at p<0.005). The results of this study indicated that quality attributes have no, or a limited role in setting market prices for most feed types in the Ethiopian feed market. The fact that both good and poor-quality feeds are sold under the same label and market value affects both traders and livestock producers. Therefore, it is important to build national feed analytical capabilities to allow quality of feeds to be checked against national feed standards, particularly for concentrate feeds.